Computer and computing technologies in agriculture ii : the second IFIP international conference on computer and computing technologies in agriculture (CCTA2008), October 18-20, 2008, Beijing, China - Li, Daoliang; Zhao, Chunjiang , 1964- (IFIP - the International Federation for Information Processing, 2009)
Constitutes the refereed proceedings of the 2nd IFIP International Conference on Computer and Computing Technologies in Agriculture. This title also features proceedings and post-proceedings of refereed international conferences in computer science and interdisciplinary fields